(untitled) (International Journal of Engineering and Computer Science, 2017)
Cloud computing promises to significantly change the way we use computers and access and store our personal and business information. Because of these new computing and communication paradigm there arise data security challenges. Even though existing techniques use security mechanisms, data theft attacks prevention fails. To overcome this we can use decoy technology to secure data stored in cloud. Although, Fog Computing is defined as the extension of the Cloud Computing paradigm, its distinctive characteristics in the location sensitivity, wireless connectivity, and geographical accessibility create new security and forensics issues and challenges which have not been well studied in Cloud security and Cloud forensics. We monitor data access in the cloud and detect abnormal data access patterns. When unauthorized access is suspected and then verified using challenge questions, we launch a disinformation attack by returning large amounts of decoy information to the attacker. This protects against the misuse of the user’s real data. Experiments conducted in a local file setting provide evidence that this approach may provide unprecedented levels of user data security in a Cloud environment